Specific lift-up behaviour of acetate-intercalated layered yttrium hydroxide interlayer in water: application for heterogeneous Brønsted base catalysts toward Knoevenagel reactions. Issue 7 (4th February 2022) - Hara, Takayoshi; Habe, Maoko; Nakanishi, Hikaru; Fujimura, Takuya; Sasai, Ryo; Moriyoshi, Chikako; Kawaguchi, Shogo; Ichikuni, Nobuyuki; Shimazu, Shogo
Abstract : The basal (00 l ) plane of acetate-intercalated layered yttrium hydroxide (CH3 COO − /Y-LRH), synthesised by an anion exchange using Cl − /Y-LRH as a parent material, increased in water, and the lifted-up layered structure was generated immediately. Abstract : Various alkylcarboxylate-intercalated layered yttrium hydroxides (C n −1 H2 n −1 COO − /Y-layered rare-earth hydroxide (LRH), n = 1–10) were synthesised by a simple anion exchange method using Cl − /Y-LRH as a parent material. The anion exchange from Cl − into CH3 COO − proceeded rapidly, as confirmed by the time-resolved synchrotron-radiation X-ray diffraction ( t -SXRD) analysis. The interlayer distance of C n −1 H2 n −1 COO − /Y-LRH could be controlled precisely, and the basal spacings calculated from XRD were linearly proportional to the length of alkyl groups. In water solvent, the basal spacing of the CH3 COO − /Y-LRH catalyst based on the (00 l ) plane increased from 1.00 nm under dry conditions to 1.35 nm, and this lifted-up layered structure was generated immediately. By use of the CH3 COO − /Y-LRH catalyst, a wide range of substrates were converted into the corresponding α, β-unsaturated nitriles in water via Knoevenagel condensation. Our synthesised heterogeneous catalyst acted as a Brønsted base for this organic transformation, and it was reusable without any loss of its catalytic activity and selectivity.